How Important Are Risk-Taking Incentives in Executive Compensation? - Ingolf Dittmann; Ko-Chia Yu (Tinbergen Institute, 2009)
This paper investigates whether observed executive compensation contracts are designed to provide risk-taking incentives in addition to effort incentives. We develop a stylized principal-agent model that captures the interdependence between firm risk and managerial incentives. We calibrate the model to individual CEO data and show that it can explain observed compensation practice surprisingly well. In particular, it justifies large option holdings and high base salaries. Our analysis suggests that options should be issued in the money. If tax effects are taken into account, the model is consistent with the almost uniform use of at-the-money stock options. We conclude that the provision of risk-taking incentives is a major objective in executive compensation practice.
Keywords: G30; M52; 330; Stock Options; Executive Compensation; Effort Aversion; Risk-Taking Incentives; Optimal Strike Price; Aktienoption; Führungskräfte; Risikopräferenz; Leistungsanreiz